OCIAD1 and prohibitins regulate the stability of the TIM23 protein translocase - Praveenraj Elancheliyan; Klaudia K. Maruszczak; Remigiusz Adam Serwa; Till Stephan; Ahmet Sadik Gulgec; Mayra A. Borrero-Landazabal; Sonia Ngati; Aleksandra Gosk; Stefan Jakobs; Michal Wasilewski; Agnieszka Chacinska (Cell Reports)
Summary: Mitochondrial proteins are transported and sorted to the matrix or inner mitochondrial membrane by the presequence translocase TIM23. In yeast, this essential and highly conserved machinery is composed of the core subunits Tim23 and Tim17. The architecture, assembly, and regulation of the human TIM23 complex are poorly characterized. The human genome encodes two paralogs, TIMM17A and TIMM17B. Here, we describe an unexpected role of the ovarian cancer immunoreactive antigen domain-containing protein 1 (OCIAD1) and the prohibitin complex in the biogenesis of human TIM23. Prohibitins were required to stabilize both the TIMM17A- and TIMM17B-containing variants of the translocase. Interestingly, OCIAD1 assembled with the prohibitin complex to protect the TIMM17A variant from degradation by the YME1L protease. The expression of OCIAD1 was in turn regulated by the status of the TIM23 complex. We postulate that OCIAD1 together with prohibitins constitute a regulatory axis that differentially regulates variants of human TIM23.